An Efficient Key Scheme for Multiple Access of JPEG 2000 and Motion JPEG 2000 Enabling Truncations - Yang, Yang; Zhu, Bin Benjamin; Li, Shipeng (IEEE Consumer Communications and Networking Conference, 2006)
JPEG 2000 provides multiple scalable accesses to a single codestream. Digital Rights Management of a JPEG 2000 codestream should preserve the original flexibility of scalability yet provide a mechanism to ensure what you see is what you pay: a low resolution version displayed on a smart phone should pay less than a high resolution version displayed on a PC. We present an efficient key scheme for multi-type, multi-level scalable access control for JPEG 2000 and motion JPEG 2000 codestreams. The scheme is based on a poset representation of the scalable access control and a hash based hierarchical access key scheme, both proposed elsewhere. The proposed key scheme exploits the information contained in a codestream and the features invariant under truncations to minimize the file size overhead for DRM applications yet preserve correct derivation of keys for descendants even when an encrypted codestream is truncated.